OUTBURGHERS AND PALEBURGHERS IN GERMAN CITIES DURING THE XIV-XV CENTURIES (City: History, Culture, Society, 2020)
The social composition of the German cities of the late Middle Ages included not only citizens living directly on the territory of the burg. A number of economic, political and military factors caused the requirement for the city authorities to attract as new burghers, people from the territories adjacent to the city, and people who do not live in cities. In the regulatory legal acts of the central government and cities, they are designated as “paleburghers” and “outburghers”. The first category of such citizens was mainly represented by the noble people and upper clergy, and the second by the peasants and the lower strata of the society in Late Medieval Germany.This article researches the main development tendencies of these two social categories of German cities of the XIV-XV centuries, their terminological definition in historiography, representation in the sources, controversial points regarding the double designation of terms, social status and legal regulation, both from the side of the city and from central authorities, differences in their relations with cities and central administration, as well as exceptions to the designation of these terms in the burgher environment of different cities. It also discusses the main processes for regulating the payment of taxes by outburghers and paleburghers, financial payments that could be provided by cities for these social groups. The author analyzes the reasons for the liquidation of these categories of the population in the late medieval German city, the confrontation that arose between city councils and the nobility about the existence of such groups of society, the possibility of further resolving these issues, as well as the conditions for their transition to the status of full-fledged burghers.
Keywords: Late Medieval city; outburghers; paleburghers; social development